MANAGEMENT OF COGNITIVE ACTIVITIES OF PREPARATORY DEPARTMENTS FOREIGN STUDENTS AT HIGHER EDUCATIONAL INSTITUTIONS OF UKRAINE WHEN STUDYING GENERAL DISCIPLINES - Olexandr O. Kalenyk; Iryna V. Ovsiienko; Tetiana L. Tsaregradskaya (Alfred Nobel University Publisher, 2021)
In modern conditions of competition in the market of educational services and their export, the system of strategic education management requires the design of a management model for all departments of the educational institution. Preparatory departments for foreign students are an important structural component of the educational process at leading universities in Ukraine. The public's request for an increase in the number of foreigners studying in Ukraine, competitive positions in their training, in particular at preparatory departments, actualizes the issue of finding a systemic, activity-based, effective approach to improve the quality of their training. Taking into account modern methodological approaches to the management system (target, system and process), the problem of finding effective ways to optimize the educational process based on the use of elements of management theory is outlined. A structuralmeaningful model of managing the cognitive activity of foreign students in the subject-meaningful and linguistic aspects of the study of general education disciplines has been developed. The stages of the management cycle are considered, taking into account the peculiarities of the training system for foreign citizens at the preparatory departments. On the example of the organization of the training system at the preparatory department of Taras Shevchenko National University of Kiev, the peculiarities of the management of the cognitive activity of students are revealed, taking into account the theoretical and methodological approaches to the general problem of the management of the educational process. To implement this approach, it is necessary to complete the main stages of the management cycle: determination of the management object; formulation of goals and objectives; fixing the initial level of the control object; the formulation of a program of action; definition of feedback channels by which the results of management will be determined; analysis of the received information according to certain parameters; correction of the initial concept and subsequent actions. The preparation of foreign students for studying at universities should take place through interdisciplinary integration of basic disciplines with professionally oriented language learning and using the latest information technologies for the individualization of training. An important aspect of the management of cognitive activity is the creation of a qualitatively new organizational and educational-methodological foundation of education based on the correction of curricula, work programs, manuals, the development of mono-technologies for a different contingent of foreign citizens.